How to Target Small-Molecule Fluorescent Imaging Probes to the Plasma Membrane—The Influence and QSAR Modelling of Amphiphilicity, Lipophilicity, and Flip-Flop - Richard W. Horobin; Juan C. Stockert (Molecules, 2023)
Many new fluorescent probes targeting the plasma membrane (PM) of living cells are currently being described. Such probes are carefully designed to report on relevant membrane features, but oddly, the structural features required for effective and selective targeting of PM often receive less attention, constituting a lacuna in the molecular design process. We aim to rectify this by clarifying how the amphiphilicity and lipophilicity of a probe, together with the tendency to flip-flop across the membrane, contribute to selective PM accumulation. A simplistic decision-rule QSAR model has been devised that predicts the accumulation/non-accumulation of small-molecule fluorescent probes in the PM. The model was based on probe log P plus various derived measures, allowing the roles of amphiphilicity, lipophilicity, and flip-flop to be taken into account. The validity and wide applicability of the model were demonstrated by evaluating its ability to predict amphiphilicity or PM accumulation patterns in surfactants, drugs, saponins, and PM probes. It is hoped that the model will aid in the more efficient design of effective PM probes.